Social support and psychological well-being among delinquents in rehabilitation centers in Malaysia - Mansor, Mariani; Abu Samah, Asnarulkhadi; Zainal Abidin, Filzah Nashua (Human Resource Management Academic Research Society, 2017)
This paper demonstrate the relationship between social support and psychological well-being of 240 delinquents in six rehabilitation centers in Klang Valley and Melaka. 113 males and 127 females delinquents aged between 10-18 years old were involved in this study. Multidimensional Scale of Perceived Social Support (MSPSS) (Zimet, Dahlem, Zimet & Farley, 1988) and Affect Balance Scale (Bradburn, 1969) were used to assess respondents social support and psychological well- being. Findings showed that majority of the respondents exhibit high level of perceive social support and moderate level of psychological well-being. Further analysis showed that social support were found to have a significant correlation with psychological well-being.